Long term prognosis of heart failure after acute coronary syndromes without ST elevation. Issue 963 (5th January 2006) - Shibata, M C; Collinson, J; Taneja, A K; Bakhai, A; Flather, M D
Abstract : Background: Information about long term outcomes of patients with acute coronary syndromes (ACS) who have clinically diagnosed heart failure is scarce. Methods: In a UK registry, this study evaluated patients with non-ST elevation ACS, recording treatment, and clinical outcomes for six months. In a subgroup, a four year mortality follow up was performed to estimate the impact of the clinical diagnosis of heart failure on survival. Results: Of 1046 patients, 139 (13%) had a history of clinically diagnosed heart failure. At discharge, ACE inhibitors were prescribed for 58% and 28%, of those with and without a history of heart failure respectively (p<0.001). Rates of angiography, percutaneous intervention, and coronary artery bypass graft were 17.3% and 29.2% (p = 0.003), 5.0% and 8.4% (p = 0.17), and 5.0% and 7.5% (p = 0.3) for these groups respectively. Death or new myocardial infarction at six months occurred in 22% and 10% (p<0.001) and at four years death occurred in 60% and 20% of these groups respectively (p<0.001). In a multivariate analysis prior heart failure carried an odds ratio of 2.0 (p = 0.001) for death or myocardial infarction at six months and 2.4 (p<0.001) for death over four years. New heart failure was associated with an increased risk of death at six months (20% compared with 5%, p<0.001). Conclusion: A clinical history of heart failure carries a substantial risk of death in patients admitted with ACS without ST elevation. Nearly 60% of those with prior heart failure are dead after four years. After adjustment for confounding factors, prior heart failure more than doubles the risk compared with those with no history.